Thermal unrest of a fumarolic field tracked using VIIRS imaging bands: The case of La fossa crater (Vulcano Island, Italy) - Coppola, D.; Laiolo, M.; Campus, A.; Massimetti, F. (Frontiers in Earth Science, 2022)
We report the results of a detailed analysis of VIIRS (Visible Infrared Imaging Radiometer Suite) imaging bands (at 375 m spatial resolution) focused on detecting thermal anomalies at La Fossa crater (Vulcano Island, Italy) over the past decade (2012-2022). The application of the MIROVA (Middle Infrared Observation of Volcanic Activity) algorithm to the VIIRS dataset allowed to measure the Volcanic Radiative Power (VRP) emitted by the fumarolic areas and to timely detect a phase of major unrest started in September 2021 (still ongoing at the time of this writing). The analysis of 10 years of data reveals that thermal emissions are characterized by a long-term VRP of 0.17 MW (baseline). This steady-state regime was perturbed in 2020-2021 when a prolonged period of lower than normal (<-2) radiant flux preceded the major unrest phase that began in mid-September 2021. By early October the anomalous VRP had peaked at 1.2 MW (6-8 times the baseline) and then started to gradually decline in the following months. A subsequent thermal pulse was recorded in May-July 2022 and was accompanied by a period of seawater discoloration that affected the Baia di Levante (a shallow sea bay 1.4 km north of the crater). The concomitance of these phenomena suggests the occurrence of a second pressurization phase driven by the arrival of deep magmatic fluids within both the central and distal degassing fumarolic zones. The analysis of VIIRS data presented here opens new frontiers in detecting unrest at quiescent volcanoes, especially those characterized by high-temperature fumarolic activity.